The Difference between in a 5K race running on the Tartan Track and the Asphalt Road Track against the Injury Risk on the Men Athletic Club of Dragon and Pandawa Salatiga - Nugrahani Febrina Sari; Agus Kristiyanto; Sri Santoso Sabarini (BIRCU, 2020)
The purpose of this study was to determine the difference between 5K long distance running on the Tartan track and the Asphalt Highway on the risk of injury to the Men’s Athlete Club of Dragon Athletics and Pandawa Salatiga. This study uses a descriptive qualitative research method using an ex post facto approach in which data taken on respondents based on events that have been experienced before. The number of samples was 14 Men’s Athlete of Pandawa Club and 10 Men’s Athlete of Dragon Salatiga Club. The total number of samples was 34 athletes and samples were taken using purposive sampling technique. Data collection techniques using Triangulation techniques, namely questionnaire or questionnaire, interviews and documentation. The validity of the questionnaire test or questionnaire was carried out and agreed upon by experts in the field of running injuries and linguists (Expert Judgment) and the hypothesis was tested using the Chi Square test with SPSS. Observation was carried out for four weeks by taking data through questionnaires and interviews by researchers to respondents or research samples namely athletes and trainers. The results of this study indicate that the asphalt highway running track has a higher risk of injury than running on the tartan track. Asphalt highway has a hard structure on the surface, when running footstool meets a hard surface so this will cause the risk of injury to the foot such as archilles tendinitis injuries where large tendon muscles behind the ankles that connect the calf muscles to the heel bones experience irritation or inflammation. Knowing the risk of injury that occurs in certain types of trajectories can help athletes and coaches in designing training programs and minimize injury.